Dynamic Studies ofSteam Methane Reformer (SMR) in Ammonia Plant - Mohammad Nazir, Norzuliana (Universiti Teknologi PETRONAS, 2009)
Mathematical modelingand simulation of Steam MethaneReformer(SMR)over sulfide nickel catalyst on alumina support has been studied. It is consists of primary and secondary reformers which is playan important role in the production of ammonia. This study consists of chemical reaction kinetics; chemical reaction equation and rate constants for a given catalyst; to develop a mathematical model for a steam reformer incorporating the reaction kinetics; to study the behavior of the reactor for changes in different variables such as feed rate, feed composition, temperature, etc. iv